FREQUENCY OF PELVIC PATHOLOGIES IN PRIMARY SUBFERTILITY ON DIAGNOSTIC LAPAROSCOPY - ANDLEEB , G; MUZAFFAR , A; PARVEEN , S; MALIK , SA (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the frequency of pelvic pathologies in female primary subfertility by using diagnostic laparoscopy. A prospective study was conducted in the Department of Gynecology and Obstetrics of Nishtar Hospital, Multan, from April 2022- April 2023. A total of 100 women aged 20-40 years who were unable to get pregnant after unprotected sex for one year and had a normal pelvic examination and semen analysis of the husband were selected for the study. All the patients underwent laparoscopy. A tubal patency test was performed by using methylene blue dye. 50 patients (50%) had been subfertile for 1-5 years. Laparoscopy revealed that endometriosis was the most common cause of subfertility, as seen in 40% of patients. Tubal blockage was also observed in 8 patients (8%). Based on the results, it can be concluded that endometriosis followed and tubal occlusions are the most common causes of subfertility in women.